The relationship between family functioning and depression among adolescents in China during the normalization stage of the COVID-19 epidemic: The mediating role of resilience - Yameng Feng; Yang Zhou; Wenzhen Li; Qingzhou Cheng; Cen Gao; Shu Yan; Na Lv; Yaofei Xie; Taimin Wu; Rong Nie; Hongping Zhang; Dajie Chen (PLoS ONE, 2025)
Background In May 2020, China shifted its COVID-19 pandemic prevention and control status from “emergency” to “regularization”. However, thus far, limited research has investigated the mental health of adolescents in Wuhan during this phase. This study examined the mental health status of adolescents in Wuhan during the regular prevention and control against COVID-19 period and explored whether psychological resilience mediated the relationship between adolescent family functioning and depression. Methods A cross - sectional survey was conducted from September to December 2022 in Wuhan. Using a census methodology, 2,410 students from a secondary vocational school were recruited for the study. Multivariate logistic regression was performed to investigate the independent effect of family functioning and psychological resilience on adolescent depression. Structural equation modeling was used to analyze the mediating role of psychological resilience in the relationship between family functioning and depression. Results The detection rate of depression among adolescent students was 35.77%. Both family functioning and psychological resilience were significantly and negatively associated with the prevalence of depression, with OR=0.800 (95%CI: 0.772–0.830) and OR=0.950 (95%CI: 0.938–0.962) respectively. Family functioning was not only directly related to depression (β = -0.575 [95% CI: -0.655, -0.505]), but also through the mediating effect of psychological resilience (β = -0.135 [95% CI: -0.173, -0.099]). Psychological resilience partially mediated the effect of family functioning on depression, with the mediating effect accounting for 19.72% of the total effect. Conclusions The COVID-19 pandemic has substantially exacerbated mental health issues among adolescents in Wuhan, China and further attention is required. The detrimental impact of poor family functioning on adolescents’ depression may be reduced by fostering psychological resilience.